Legal Heuristics and the Positivisation of Law in Dogmatic Discourse - Leszczyński, Jerzy (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The general opinion that the text of the law does not imply its use leads to an understanding of the role that legal dogmatics and legal practice can play in solving this problem. Common thematic field of both those lawyers’ activities allows us to distinguish a dogmatic discourse, by which and in which the law is positivised by consolidating applicable (operative) patterns of solving legal problems. These patterns are created by referring to the aspects of text, language, and system of law, but also to the history of the discourse. The positivisation of law is the result of specific legal heuristics, consisting in combining meanings, expectations, values, and existing practices in solving legal problems. Legal heuristics does not boil down to a method, but, rather, is a framework, a context, and a set of conditions for cognition aimed at solving practical problems.